An analysis of China's liberalisation Policy with respect to international air transport - Zhang, Bixiu (Cranfield University, 2010)
International air transport is a commercial business by nature but carries a political significance. It has been regulated under the Chicago regime which requires the sovereignty governments to negotiate and determine how airlines engage in the transnational operations regardless of the market demand. Policy makers will have to take into account all factors, whether at international, domestic, institutional and individual levels, in determining to what extent the market should be liberalised so as to protect their national interest, optimise the opportunities for their industry and society as a whole, while at the same time promote competition and facilitate international trade. Despite the vast research that has been done on the liberalisation of international air transport as well as China‘s aviation policy and its industry, little is known about the considerations of Chinese government when formulating its international air transport policy, e.g. what are the variables that have influenced the country‘s policy making process that leads to the policy per se. The focus of the existing literature fails to treat China‘s international air transport policy as a subject matter for an objective and comprehensive analysis, but rather takes the policy itself as an external stimulus that drives the radical changes of the industry. Consequently, China‘s policymaking process with respect to international air transport remains a black box and its international behaviour is considered unpredictable. Applying the Micro-Macro Linkage Approach to three case studies, i.e. China-the US, China-the Netherlands and China-the UK markets, this research analyses China‘s liberalisation policy with respect to international air transport. By examining the data gathered through qualitative methods such as historical files and record, observations, and interviews with those who have participated in the process of policymaking and have been personally involved in bilateral air services negotiations, this research aims at identifying the factors that have had an impact on the country‘s policymaking process, establishing whether these factors are evolving over the years and determining how they are interacting with each other in leading to the policy outcome, hence, shedding light on the country‘s international trade policymaking and its international behaviour. The research has revealed that China‘s international air transport policymaking is both a top-down and bottom-up process with industry regulator being the primary initiator, formulator and administrator of the industry-specific liberalisation policy. Its decision making process has become more transparent, plural, open for and subject to both external and internal influences at all levels. International environment including international conventions, laws and regulations have formed a framework within which the country has to operate to develop its overall national policy. Bilateral political and economic relationship has played a pivotal role in shaping the country‘s policy on that specific country-pair market. Domestic considerations such as national interest, benefits to the society, industry and consumers as a whole are the fundamental concerns in determining the policy scope, i.e. to what extent the market should be liberalised and the pace of such liberalisation. Stakeholders are increasingly proactive in its involvement in the policymaking process in an attempt to influence the policy makers to their own optimal benefits. Institutions and personal characteristics do shape individual policy makers‘ mindset and perceptions but only to the extent of affecting the negotiation outcome on the bilateral country-pair markets. These factors have been evolving over the years and are time- and circumstance-constrained, namely, some factors may function at one occasion at a certain time but not necessarily at another. This research is a meaningful endeavour in attempting to understand China‘s policymaking process with respect to international air transport as an international trade in services, which has just received growing interest in both academia and industry practitioners in recent years. It will contribute to the knowledge of the study of China and the study of international air transport at large.
Keywords: China; liberalisation; international air transport; trade in services; policymaking